DISKURSUS MANAJEMEN BENCANA ERA COVID-19 - Burhanudin Mukhamad Faturahman (Universitas Islam Darul Ulum Lamongan, 2021)
Disaster management is a series of disaster cycles including pre-disaster, emergency, and post-disaster response stages with different handling characteristics at each stage. Based on these stages, the covid-19 disaster event has special characteristics where the non-natural disaster has a disaster emergency status as well as a recovery stage. The occurrence of two stages of a disaster at once in one disaster event causes obscurity and poor policy coordination in the emergency response period. The lack of the role of BNPB and BPBD during the disaster emergency caused policies to become conflicted between the health sector and the economic sector. Therefore, it is necessary to revise the disaster management law by strengthening the role of bnpb coordination as the main actor in mobilizing strategic resources both technical and non-technical. The revision of the disaster management law may refer to local government laws to harmonize disaster emergency policies at the central and regional levels. In addition, collaboration with academics is important to provide health resources for handling covid-19 in the country in the production, distribution, and consumption process.